Development and evaluation of an online training for paraprofessional nutrition educators from the expanded food and nutrition education program (EFNEP) addressing prenatal nutrition - Chlipalski, Micheline, author; Baker, Susan, advisor; Auld, Garry, advisor; Olson, Beth, committee member; Quick, Don, committee member (Colorado State University. Libraries, 2016)
The objective of this research project was to assess the training needs of paraprofessional nutrition educators from the Expanded Food and Nutrition Education Program (EFNEP), as well as to develop and evaluate an online training for these paraprofessionals using the prenatal nutrition lesson from the Eating Smart • Being Active (ESBA) curriculum. Different study designs were used throughout this research, subdividing the project in three phases: “Phase I” was a qualitative cross-sectional study. Semi-structured, in-depth interviews were done with 15 paraprofessional educators and 7 supervisors. “Phase II” corresponded to the design and development of a video based online training using instructional design principles and the Cognitive Theory of Multimedia Learning. “Phase III” was a quasi-experimental pre-/post-test research design with 139 paraprofessionals from 18 states/US territories who were randomly assigned, by state, to either intervention or control group to implement and evaluate the online training. Assessments for Phase III included knowledge, ability to identify inappropriate teaching practices demonstrated in videos, teaching self-efficacy, and a reaction survey to gather opinions of paraprofessionals after completing the online training. Results from “Phase I” included: almost all interviewees considered that having an online training would be beneficial. Most paraprofessionals and supervisors wanted the online training to compliment, not replace, in-person trainings. The preferred format was videos depicting role plays by educators teaching the lesson. Results from “Phase II” included: forty short video clips developed to present key aspects of delivering the prenatal lesson. Finally, results from “Phase III” included: significantly higher scores in the intervention group in knowledge, identification of inappropriate practices, and teaching self-efficacy compared to the control group. More than 85% of paraprofessionals who completed the training considered that the online training helped them feel better prepared to teach the ESBA prenatal lesson, would recommend the training to other paraprofessional nutrition educators, and would like more online trainings like this one in the future. In conclusion, a video based online training is an effective method to train paraprofessional nutrition educators on how to teach a nutrition lesson plan, in terms of increased knowledge, identification of proper practices, and self-efficacy. A large number of educators, geographically dispersed, can be easily reached with this training delivery method helping standardize current trainings.